Pengaruh Kombinasi Substrat dan Lama Waktu Inkubasi Berbeda Fermentasi Menggunakan Aspergillus ficuum terhadap Aktivitas Enzim dan Perubahan Kandungan Nutrisi - W. A. Angga; Y. Rizal; M. E. Mahata; A. Yuniza; R. Mayerni (Jurnal Peternakan, 2020)
Physical processing such as immersion at different water temperatures did not improve crude fibre and crude protein content of wasted-tea leaves. Thus, the utilization of these wasted tea leaves for poultry diet is still limited due to the high in crude fibre content. Therefore, it is necessary to find out a method for solving this problem. One of the methods is a fermentation by using Aspergillus ficuum. This fungi is known as a microbe which produces cellulase for reducing fibre content. The objectives to investigate the appropriate rice bran (RB) and wasted tea leaf (WTL) combinations and incubation times when fermented with Aspergillus ficuum, and to study the effects of this fermentation process on enzymes (cellulase and protease) activity, and alteration of dry matter, crude fibre and crude protein contents. This experiment was performed in a completely randomized design in a 4 x 2 factorial arrangement of treatments with 4 replicates. The first factor was RB and WTL combination as follows: 100:0% (A1), 90:10% (A2), 80:20% (A3), 70:30% (A4). The second factor was incubation times as follows: 7 days (B1) and 9 days (B2). These combinations of RB and WTL were fermented by using Aspergillus ficuum at the dose of 6.3 x 1012 CFU/mL. Measured variables were cellulase and protease activities, and alteration percentage in dry matter (DM), crude fibre (CF) and crude protein (CP). There was an interaction between RB:WTL combination and incubation time in cellulase activity (P<0.01) and CF content (P<0.01). Increasing WTL up to 10% in RB: WTL combination significantly augmented (P<0.05) cellulase activity at 9 days incubation time. The reduction percentage in CF occurred at 90:10% RB and TLM combination and 9 days incubation time. The incubation time for 9 days decreased the protease activity (P<0.01) as well as the reduction percentage in DM (P<0.05). The 90:10% RB and WTL combination improved the increasing percentage in CP (P<0.01). In conclusion, the appropriate RB and WTL combination and incubation time for fermenting the combination ratio of RB:WTL by using Aspergillus ficuum was 90:10% at 9 days incubation time.